La Traviata à brasileira: diálogos culturais na sambópera de Augusto Boal - Hellem Pimentel Santos (2011)
The aim of this paper is to present a study showing the characteristics that underlie the gender created by Augusto Boal in 1999 called sambópera and identify the elements that conceptualize it as a multicultural gender, putting into perspective such concepts as hybridity, identity and the concept of opera as musical theater. Sambópera consists in rereading operas of classic-romantic tradition, contextualizing them culturally. This rereading, besides being a social critic, discusses the issue of multiculturalism within the Brazilian society. Taking as an object of research the work "A Traviata: A Metáfora do Desejo (2002), we assume that sambópera is a cultural gender, result of Boal experience in exile, and that is part of the artistic context built in post-modernity, signaling to the plural, for multiplicity. From the methodological point of view we related the documentary sources with the audio-visual sources, in order to identify how Boal, along with Marcos Leite, Jayme Vignoli and Celso Branco have developed multiculturalism in the creation of sambópera.